The Sage encyclopedia of intellectual and developmental disorders - Braaten, Ellen (Thousand Oaks, California : SAGE, 2018)
According to the CDC'about one in six, or about 15%, of children aged 3 through 17 years have one or more developmental disabilities,' such as ADHD, autism spectrum disorders, cerebral palsy, intellectual disability, learning disability. Intellectual disorders are characterized by significant limitations in both intellectual functioning and in adaptive behavior, which covers many everyday social and practical skills, impacting learning, reasoning, problem solving, and other cognitive processes. These disabilities originate before the age of 18 and continue across the life span. Developmental disorders are chronic disabilities that can be cognitive or physical or both. The disabilities appear before the age of 22 and are likely to progress across the lifespan.
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Mental retardation -- Encyclopedias; Developmental disabilities -- Encyclopedias